Preparation of artificial L-shaped canals with nickel-titanium rotary files* - Radwański, Mateusz; Łęski, Michał; Pawlicka, Halina (Journal of Stomatology, 2017)
Introduction. The aim of endodontic treatment is to remove the pulp and to shape the root canal with respect to the original anatomy. In order to shorten the working time and to reduce the risk of procedural errors, nickel-titanium rotary files are used in canal preparation. The rotary instruments vary in taper, cross-sections of working parts, manufacturing process, as well as direction and extent of rotation during shaping. Aim of the study. To compare the shaping ability of three rotary instruments in simulated L-curved canals. Material and methods. Thirty resin blocks with simulated L-curved canals were used in this experimental study. The blocks were divided into three groups (ten blocks in each). The canals were prepared to an apical size 25 according to the manufacturer’s recommendations. Pre-operative and post-operative photographs were taken and images were superimposed by using the GIMP 2.6 program. The amount of material removed from canal walls, apical transportation and changes in the working length were measured. Results. The most central preparation was provided by WaveOne Gold as compared to the other systems. The smallest change in the working length was noted after Hyflex CM instrumentation. The statistically significant differences were detected between ProTaper Universal and Hyflex CM, and between ProTaper Universal and WaveOne Gold files